2014
DOI: 10.1371/journal.pone.0091127
|View full text |Cite
|
Sign up to set email alerts
|

Altered Lipid Homeostasis in Sertoli Cells Stressed by Mild Hyperthermia

Abstract: Spermatogenesis is known to be vulnerable to temperature. Exposures of rat testis to moderate hyperthermia result in loss of germ cells with survival of Sertoli cells (SC). Because SC provide structural and metabolic support to germ cells, our aim was to test the hypothesis that these exposures affect SC functions, thus contributing to germ cell damage. In vivo, regularly repeated exposures (one of 15 min per day, once a day during 5 days) of rat testes to 43°C led to accumulation of neutral lipids. This SC-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…Spermatogenesis is a complex process that involves the development of spermatozoa in the seminal tubules. The differentiation of spermatogonia into spermatozoa requires the participation of several cell types and the correct FA profile that contributes to a normal spermatogenetic process [117]. The importance of lipid composition, especially phospholipids, in the plasma membrane and semen plasma for spermatozoon function has since long been recognized [72].…”
Section: Discussionmentioning
confidence: 99%
“…Spermatogenesis is a complex process that involves the development of spermatozoa in the seminal tubules. The differentiation of spermatogonia into spermatozoa requires the participation of several cell types and the correct FA profile that contributes to a normal spermatogenetic process [117]. The importance of lipid composition, especially phospholipids, in the plasma membrane and semen plasma for spermatozoon function has since long been recognized [72].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, all the concentrations of leptin decrease acetate production by Sertoli cells (Martins et al 2015), which could be associated with alteration in the cells lipid droplet accumulation. Accumulation of cytoplasmic lipid droplets, which has been associated with the elimination of germ cell-derived apoptotic bodies by phagocytosis (Wang et al 2006), was reported as one of the most striking deleterious effects of hyperthermia in Sertoli cells (Valles et al 2014). Interestingly, accumulation Ghrelin is produced in the gastrointestinal tract and impairs the testicular function by disrupting both the hypothalamic-pituitarythyroid (HPT) axis, affecting Sertoli and Leydig cell functions.…”
Section: Energy Balance Hormonal Dysfunction and Male Reproductionmentioning
confidence: 99%
“…They are incorporated into maturing germ cells by lysophosphatidic acid acyltransferase 3 [7]. An improper FA profile modifies the function of Sertoli cells as spermatogenesis supporters, influencing germ cell apoptosis [8]. Furthermore, during epididymal maturation, the lipid composition of the sperm membrane is remodelled and the saturation of FA increases from caput to the cauda epididymis, while the proportion of PUFA remains similar [9].…”
Section: Introductionmentioning
confidence: 99%